The Relationship Between Parents’ Level Of Knowledge About Acute Respiratory Infection (ARI) And Preventive Behaviors Toward Ari Among Under-Five Children - Ni Kadek Shintya Putri Diah Pitaloka; Ni Wayan Trisnadewi; AA Istri Dalem Hana Yundari (Jurnal Medicare, 2026)
Acute Respiratory Infection (ARI) remains a leading cause of morbidity and mortality among children under five, accounting for approximately 20% of under-five deaths in 2024. Parental knowledge is considered an important factor influencing ARI prevention practices. This study aimed to analyze the relationship between parental knowledge of ARI and ARI prevention behavior among children under five at UPTD Puskesmas III South Denpasar. This study employed a correlational analytic design with a cross-sectional approach. A total of 92 parents of children aged 1–4 years were selected using purposive sampling. Data were collected using structured questionnaires and analyzed using the Spearman's rank correlation test. The results showed that most respondents had good knowledge of ARI and demonstrated good preventive behaviors. Spearman's rank analysis revealed a significant positive relationship between parental knowledge and ARI prevention behavior (p < 0.05; r = 0.393). It can be concluded that higher parental knowledge is associated with better ARI prevention behavior among children under five. Therefore, continuous health education is needed to improve parents' knowledge and strengthen ARI prevention practices.